(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Contribution of Women Fruit Traders in Supporting Family Income at Badung Market, Denpasar City. In its development, women are seen as more suitable to work in the informal sector because they only require relatively small capital and flexible working hours, thus enabling both married and unmarried women to earn additional income, such as fruit sellers in Badung Market, Denpasar City. The contribution of women as fruit sellers in supporting their household income can be seen from the proportion of the percentage of women’s income as fruit sellers to their household income. The aims of this study were (1) to analyze the income of women fruit sellers in Pasar Badung, and (2) to analyze how much the income of women fruit sellers contributed to their household income. This study used 50 female fruit traders as respondents. The results of this study indicate that the average monthly income of women fruit sellers in Badung Market is Rp6.236.177.. The income contribution of women as fruit sellers in Pasar Badung is 47% of their household income. The advice that can be given to women fruit sellers in Badung Market is that they are expected to be able to make simple sales records and utilize digital platforms to market their fruit wares. As well as being able to maintain their jobs and work in the informal sector can be a motivation and opportunity for other women who want to earn income with non-binding conditions.